Concentrated LiPF6/PC electrolyte solutions for 5-V LiNi0.5Mn1.5O4 positive electrode in lithium-ion batteries. (10th August 2016) - Doi, Takayuki; Masuhara, Rin; Hashinokuchi, Michihiro; Shimizu, Yusuke; Inaba, Minoru
Abstract: Charge and discharge properties of spinel LiNi0.5 Mn1.5 O4 positive electrodes were investigated using propylene carbonate (PC)-based concentrated electrolyte solutions in the range of 0.83 (ca. 1 mol dm −3 ) to 4.45 (nearly saturated) mol kg −1 . The solvation state of PC in the concentrated electrolyte solution was studied by Raman spectroscopy. The HOMO energy of PC in Li + (PC) n was evaluated by first-principle calculation to assess the oxidative stability of PC molecules solvating lithium ion. Charge and discharge measurements revealed that the irreversible capacity due to solvent decomposition decreased with increasing the concentration of LiPF6, while discharge capacity increased. In addition, cycle performance of LiNi0.5 Mn1.5 O4 positive electrodes was remarkably improved by the use of graphitized Ketjenblack as a conductive additive.